Chronological History of the Geography Department in the First Half of the 20th Century, China - Zhu Guifang; Li Miao; Sun Jun; Chen Shuo; Li Qiuying; He Fengyan; Zhu Siji (Redai dili)
The first half of the 20th century was a critical period in the transformation of Chinese geography from tradition to modernity. The geography departments of higher education institutions, as the main organizations for research and teaching in Chinese geography at the time, reflected the developmental trajectory of geography in China. Although research has yielded certain scholarly achievements, three notable limitations persist in current academic investigations. First, it places excessive emphasis on "establishment" events while neglecting dynamic processes, such as "disciplinary restructuring," "institutional reorganization," and "closure," thus failing to fully capture the complexity of academic department development. Second, owing to incomplete historical materials, there are significant discrepancies in the statistical counts of academic departments, which often include non-geography departments or proposed departments that were never operational. Third, insufficient attention to geography departments in normal universities and their structural transformations within the discipline has resulted in an incomplete understanding of the pathways toward disciplinary specialization. This study adopts a chronological approach that integrates and utilizes diverse sources of materials, including the National Education Yearbooks, university statistical data, admission guides, institutional historical archives, memoirs, enrollment records, and contemporary research findings. Cross-validation identifies the years of establishment, restructuring, reorganization, and closure of geography departments, thereby clarifying their founding, restructuring, reorganization and closure processes. This study further analyzes their quantitative characteristics, developmental stages, institutional affiliations, and disciplinary structures. The research findings indicate the following: 1) Regarding the number of departments established, it has been confirmed that 52 universities and colleges founded 63 geography departments, a figure significantly higher than that reported in existing studies (Approximately 40). This discrepancy arises from two aspects: on the one hand, existing studies fail to fully account for the restructuring and reorganization of geography departments; on the other hand, eight previously overlooked geography departments in universities have been included. 2) The establishment process can be divided into four stages: 1904–1928 (initial establishment period), 1929–1936 (period of minimal expansion), 1937–1945 (period of moderate expansion), and 1946–1949 (period of slow expansion). The overall trajectory across these stages is characterized by slow growth amid frequent cycles of founding, restructuring, reorganization and closure, with fewer than half of the established departments remaining operational by the end of the period. 3) Regarding departmental distribution, the majority were located in universities and normal colleges, with a high proportion in normal colleges. From 1904 to 1928, geography departments were mainly located in normal universities, whereas a new trend emerged from 1929 to 1936, with their affiliation shifting toward the faculties of science in universities. 4) Regarding the disciplinary structure, significant differences exist between different types of institutions; university geography departments are primarily aligned with geology and meteorology. Clearly defined differences in disciplinary structure can be observed across different periods, especially pronounced between 1929–1936 and 1946–1949, where independent department characteristics emerged distinctly. Normal universities display a prominent association with history and geography, with earlier instances of interdisciplinary association with Chinese literature, history, and natural sciences. Through multisource historical evidence corroboration and chronological textual research, this study comprehensively illuminates the developmental process of geography departments in China. First, it corrects the number of geography departments, highlighting the academic contributions of marginal institutions. Second, it divides development into four stages, demonstrating the impact of warfare and policies on the rise and fall of these departments. Additionally, it tracks the transition from integrated to independent systems, illustrating the process of scientific development in geography. Ultimately, these findings provide a foundational basis for researching the history of modern Chinese geography, educational policies, and academic systems, while also offering historical references for contemporary disciplinary construction and institutional planning.